Adherence And Persistence To Antidepressant Medication During Pregnancy: Does It Differ By The Class Of Antidepressant Medication Prescribed? - Kamala Adhikari Dahal; Scott Patten; Sangmin (Sarah) Lee; Amy Metcalfe (International Journal of Population Data Science, 2018)
Introduction Pregnant women are often concerned about the impact of antidepressant medication use on their pregnancy, such as congenital abnormalities. This concern may vary in a way that depends on the class of antidepressant medication prescribed.